An Alchemist in Chains The Case Against the Mystic Johann Konrad Dippel in Altona - Stjernfelt, Frederik 1957- (De Gruyter Oldenbourg, 2024)
Klappentext: How could a pious, Christian mystic spread radical Enlightenment ideas and freedom of thought? Johann Konrad Dippel was a radical pietist, an alchemist, a philosopher, a medical doctor, a renegade, a firebrand. He was also one of the most-read authors of early eighteenth-century Europe. Born at the Burg Frankenstein in the South of Germany, he was a truly cosmopolitan figure, straying between France, Berlin, the Netherlands, Denmark, Sweden, and various German states. From 1714–1719, he was in Altona near Hamburg, then the second city of Denmark-Norway. Here, a labyrinthine case was brought against him, terminating with his banishment to the Danish island of Bornholm in the Baltic Sea. This book is the first to investigate in detail the Case Against Dippel in Altona, pitting him in a struggle against the strongest noble couple of Denmark-Norway, the Reventlows, presiding in Altona. It was a case involving libel, bribes, corruption, but also branching into blasphemy and gold-making. The investigation of the Case Against Dippel is embedded in a narrative of what is known about his frantic life and defiant thought before and after his seven-years’ incarceration. The whole story throws a new light upon the challenging question of the origin of Modernity and the clandestine connections between radical pietism and radical Enlightenment.